2000
DOI: 10.1023/a:1026563313952
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Congestive heart failure may result from cardiovascular overload, from systolic or from diastolic dysfunction. Diastolic left ventricular dysfunction may result from structural resistance to filling such as induced by pericardial constraint, right ventricular compression, increased chamber stiffness (hypertrophy) and increased myocardial stiffness (fibrosis). A distinct and functional etiology of diastolic dysfunction is slow and incomplete myocardial relaxation. Relaxation may be slowed by pathological proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…This may be because of intrinsic differences in cellular processes between early and late ejection. Loading during active cross-bridge formation (early systolic load) increases the number of interacting cross-bridges (cooperative activity), 27 a physiologic mechanism that allows adequate matching of the number of cross-bridges with systolic load. However, when increased load occurs after the onset of myocardial relaxation, the number of interacting cross-bridges can no longer adapt, which results in a mismatch between the number of cross-bridges and load, and an increased stress imposed on individual cross-bridges.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be because of intrinsic differences in cellular processes between early and late ejection. Loading during active cross-bridge formation (early systolic load) increases the number of interacting cross-bridges (cooperative activity), 27 a physiologic mechanism that allows adequate matching of the number of cross-bridges with systolic load. However, when increased load occurs after the onset of myocardial relaxation, the number of interacting cross-bridges can no longer adapt, which results in a mismatch between the number of cross-bridges and load, and an increased stress imposed on individual cross-bridges.…”
Section: Discussionmentioning
confidence: 99%
“…However, when increased load occurs after the onset of myocardial relaxation, the number of interacting cross-bridges can no longer adapt, which results in a mismatch between the number of cross-bridges and load, and an increased stress imposed on individual cross-bridges. 27 Of note, the timing of transition from myocardial fiber contraction to relaxation differs from the timing of transition from ventricular systole to diastole, normally occurs early during the ejection phase, 2729 and is related to the descending limb of the myocyte cytoplasmic calcium transient. 27,28 In addition to the acute effect of late systolic load on diastolic function demonstrated in various studies, late systolic load has been shown to induce more LV remodeling and fibrosis than early systolic load.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increases in load thus produce greater increases in blood pressure, which can accentuate impairment in relaxation and diastolic stiffness and predispose to flash pulmonary edema [43, 115]. Decreases in load due to overdiuresis or vasodilators result in exaggerated decreases in blood pressure and limit the improvement in stroke volume with afterload reduction, which figures so prominently into therapeutic strategies in HFrEF (Fig.…”
Section: Cardiovascular Structure and Function In Hfpef: Integrative mentioning
confidence: 99%
“…In contrast, loads imposed late in systole do not lead to increased cross-bridges, instead increasing the load on each individual cross-bridge. This could lead to an earlier onset, but slowed rate, of relaxation(41,42) and potentially, the activation of unfavorable signaling pathways that promote maladaptive hypertrophy. Further work is needed to understand the molecular mechanisms by which late systolic load may impact myocardial remodeling and failure.…”
Section: Discussionmentioning
confidence: 99%